Obsessive compulsive symptoms in Schizophrenia: the prevalence, associated factors and clinical outcomes in University Malaya Medical Center / Ng Boon Seng - Ng , Boon Seng (2016)
There is a growing interest on the impact of comorbid obsessive compulsive symptoms on the course and severity of Schizophrenia in recent years. However, to date, there is no study on the prevalence of obsessive compulsive symptoms in Schizophrenia in Malaysia, and no study was done on their impacts. Existing literatures elsewhere showed conflicting evidences on the clinical outcomes of this comorbidity. In line with holistic care for people with chronic mental illness, recognition of the impacts of OCS on Schizophrenia would help to reduce the devastating burden on the sufferer and the family.